Armed conflicts and wildlife decline: Challenges and recommendations for effective conservation policy in the Sahara‐Sahel. Issue 5 (3rd April 2018) - Brito, José Carlos; Durant, Sarah M.; Pettorelli, Nathalie; Newby, John; Canney, Susan; Algadafi, Walid; Rabeil, Thomas; Crochet, Pierre‐André; Pleguezuelos, Juan Manuel; Wacher, Tim; de Smet, Koen; Gonçalves, Duarte Vasconcelos; et al.
Abstract: Increasing conflicts and social insecurity are expected to accelerate biodiversity decline and escalate illegal wildlife killing. Sahara‐Sahel megafauna has experienced recent continuous decline due to unsustainable hunting pressure. Here, we provide the best available data on distribution and population trends of threatened, large vertebrates, to illustrate how escalating regional conflict (565% growth since 2011) is hastening population decline in areas that were formerly refugia for megafauna. Without conservation action, the unique and iconic biodiversity of Earth's largest desert will be forever lost. We recommend: (1) establishing strong commitments for change in global attitude toward nature; (2) engraining a culture of environmental responsibility among all stakeholders; (3) fostering environmental awareness to drive societal change; (4) reinforcing regional security and firearms control; and (5) implementing local research and wildlife monitoring schemes. We identify relevant international partners needed to tackle these challenges and to make strong policy change for biodiversity conservation and regional stability.